The ministry of utmost happiness [compact disc, unabridged] - Roy, Arundhati (Penguin Random House, 2017)
An intimate journey of many years across the Indian subcontinent. The tale begins with Anjum--who used to be Aftab--unrolling a threadbare Persian carpet in a city graveyard she calls home. We encounter the odd, unforgettable Tilo and the men who loved her--including Musa, sweetheart and ex-sweetheart, lover and ex-lover; their fates are as entwined as their arms used to be and always will be. We meet Tilo's landlord, a former suitor, now an intelligence officer posted to Kabul. And then we meet the two Miss Jebeens: the first a child born in Srinagar and buried in its overcrowded Martyrs' Graveyard; the second found at midnight, abandoned on a concrete sidewalk in the heart of New Delhi.